1020 steel coated with Ti/TiN by Cathodic Arc and Ion Implantation - Bermeo, Diego Fernando (2017)
TiN coatings have been widely studied in order to improve mechanical properties of steels. In this work, thin Ti/TiN films were prepared by plasma based immersion ion implantation and deposition (PBII&D) with a cathodic arc on AISI 1020 steel substrates. Substrates were exposed to the discharge during 1 min in vacuum for the deposition of a Tiunderlayer with the aim of improving the adhesion to the substrate. Then, a TiN layer was deposited during 6 min in a nitrogen environment at a pressure of 3xl0-4 mbar. Samples were obtained at room temperature and at 300 °C, and with or without ion implantation in order to analyze differences between the effects of each treatment on the tribological properties. The mechanical and tribological properties of the films were characterized. The coatings deposited by PBII&D at 300 °C presented the highest hardness and young modulus, the best wear resistance and corrosion performance.